AB1174 The inflammatory changes at joints and enthesis in a cohort of patients affected by ochronosis: an ultrasonographic study. (12th June 2018) - Adinolfi, A.; Di Sabatino, V.; Toscano, C.; Picerno, V.; Bardelli, M.; Selvi, E.; Santucci, A.; Galeazzi, M.; Frediani, B.; Filippou, G.
Abstract : Background: The pathogenesis of Ochronosis, the musculoskeletal manifestation of alcaptonuria (AKU) is still unclear. The joint damage usually described is similar to osteoarthritis, but in some cases the spinal involvement could resemble spondiloarthritis (SpA). These findings suggest that inflammatory changes could be prevalent in some cases while degenerative aspects could be dominant in others. Objectives: To evaluate the prevalence of inflammatory changes in peripheral joints and enthesis of a cohort of patients affected by AKU. Methods: Consecutive patients with definite diagnosis of AKU referred to our clinic from 2014 to 2017 were enrolled. All patients underwent an ultrasound (US) exam of the metacarpo-phalangeal joints (MCP), proximal interphalangeal joints (PIP), radiocarpal/mid carpal joints, elbow, gleno-humeral, hip, knee, ankle and metatarso-phalangeal (MTP) joints bilaterally; flexor and extensor tendons of fingers and wrists and the ankle tendons were also examined. Further, the enthesis of the rotator cuff of the shoulder, triceps, quadriceps, patellar and Achilles tendons were assessed. Joints and tendons with a synovial sheath were assessed for effusion, synovial hypertrophy and power Doppler (PD) signal while enthesis were evaluated for the presence of PD signal, enthesophytes and calcifications. All the US lesions were scored using a dichotomous scale (presence/absence). All US exams were performed by an expert sonographer blind to clinical history, using an Esaote MyLab70 scanner equipped with high resolution linear probes. Results: We enrolled 19 patients (11 women) with a mean age of 53 yo (SD ±14, 69). Only 2 patients didn't show inflammation at any joint or tendon. The most involved joint was the knee (11/19), while regarding enthesis, the Achilles tendon (4/19) and the distal patellar tendon insertion were the most frequently involved (6/19). The mean number of joints with effusion or synovial hypertrophy was respectively equal to 2, 47 (median 2, range 1–8) and 1, 84 (median 2, range 1–7), while 0, 21 joints (median 0, range 0–2) presented also PD. The mean of the exudative tenosynovitis was 0, 47 (median 0, range 0–3), while for proliferative tenosynovitis was 0, 42 (median 0, range 0–2). The PD signal in tendons with sheaths was rare (mean 0, 16, median 0, range 0–2). Finally, the mean number of enthesis with PD was 0, 95 (median 0, range 0–7) while the mean value was 0, 37 (median 0, range 0–3) for enthesophytes and 2, 63 (median 1, range 0–9) for calcifications. Conclusions: The pathological processes that lead to the typical joint damage in ochronosis are not yet completely clarified. The results of this study showed that articular inflammation is common in these patients, sometimes associated with enthesis involvement. The role of inflammation should be further addressed as could be a new therapeutic target for this disease. Disclosure of Interest: None declared